2018
DOI: 10.1038/s41467-017-02647-1
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional spin density wave state in metallic (Sr1−xLa x )2IrO4

Abstract: Materials that exhibit both strong spin–orbit coupling and electron correlation effects are predicted to host numerous new electronic states. One prominent example is the Jeff = 1/2 Mott state in Sr2IrO4, where introducing carriers is predicted to manifest high temperature superconductivity analogous to the S = 1/2 Mott state of La2CuO4. While bulk superconductivity currently remains elusive, anomalous quasiparticle behaviors paralleling those in the cuprates such as pseudogap formation and the formation of a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 38 publications
1
40
0
Order By: Relevance
“…For the same doping a SCM appears at 60 meV. Since the spectral weight in these modes is far too high for phonons, they have to correspond to electronic (5), and E u (6) modes (see Table II), each overlapping with the energy of the SCM. Fano-type asymmetry has also been observed for the Raman active phonons in the doped material [12].…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the same doping a SCM appears at 60 meV. Since the spectral weight in these modes is far too high for phonons, they have to correspond to electronic (5), and E u (6) modes (see Table II), each overlapping with the energy of the SCM. Fano-type asymmetry has also been observed for the Raman active phonons in the doped material [12].…”
Section: Methods and Resultsmentioning
confidence: 99%
“…It has been suggested that this material can be turned into a high T c superconductor [2]. While antiferromagnetism and spin density wave order have been reported for different doping concentrations [3][4][5], up to date transport and magnetization data have not revealed superconductivity [3,6]. A recent angle resolved photoemission (ARPES) study found an anisotropic pseudogap in Sr 2−y La y IrO 4 [6].…”
Section: Introductionmentioning
confidence: 99%
“…In perovskite manganites, the parent antiferromagnetic (AFM) order develops into a ferromagnetic (FM) phase hosting giant magnetoresistance [2]. On the other hand, in both S = 1/2 cuprates [1] and J eff = 1/2 iridates [3][4][5][6], doping suppresses long-range AFM order leading to the formation of incommensurate spin-density wave order [7][8][9][10] with a conventional paramagnetic (PM) metal eventually emerging.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Sr-214 doped by electrons is thought to be a nearly perfect analogue to hole-doped cuprates (4,15). It exhibits many of the same electronic phenomena emerging with doping, such as a pseudogap (12,15,(26)(27)(28), Fermi arcs (29) and an incommensurate spin density wave (30). Although superconductivity is yet to be achieved, it has been theoretically predicted to occur at higher electron densities (31), if those were to be experimentally achieved.…”
mentioning
confidence: 99%